Modeling vegetation density with remote sensing, normalized difference vegetation index and biodiversity plants in watershed area - R.Z. Ekaputri; T. Hidayat; H.K. Surtikanti; W. Surakusumah (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: The condition of the Bengkulu watershed area is outlined in the Indonesia Integrated Watershed Management Plan. Adverse conditions in the watershed have been linked to a range of natural calamities, such as floods and droughts. Moreover, the process of converting forests into plantations or agricultural lands has resulted in environmental degradation. Therefore, there is a pressing need for an evaluation of vegetation density and plant analysis within the watershed. This is crucial for comprehending ecological conditions, devising restoration measures, and implementing conservation efforts. Hence, the aim of this study is to analyze vegetation density and track plant diversity, specifically focusing on tree characteristics, throughout.METHODS: The study techniques utilized in this investigation encompass the gathering of normalized difference vegetation index data from satellite imagery, followed by its analysis through the utilization of geographic information system software. Sentinel satellite imagery from 2021 is utilized due to its efficacy in monitoring environmental conditions and managing natural resources. Spatial data encompass maps and field data.FINDING: By employing normalized difference vegetation index data, the study pioneers a novel approach to environmental monitoring, setting an example for effective resource management and ecological conservation in watershed regions. The study findings indicate that 29 percent of the watershed area exhibits moderately steep topography with a dendritic flow pattern. The assessment of the normalized difference vegetation index demonstrates that the watershed is comprised of multiple sections abundant in high-density vegetation, primarily dedicated to plantations. Within the Bengkulu watershed area, a total of 49 tree species from 22 families were identified, with diversity indices falling within the moderate category.CONCLUSION: An in-depth knowledge of the ecological factors and plant preservation initiatives in the Bengkulu watershed can greatly aid in sustainable environmental management and help policymakers develop more effective policies for ensuring environmental sustainability. The findings of this study contribute significantly to the Global Journal of Environmental Science and Management’s goals of promoting sustainable environmental management and biodiversity preservation, offering actionable insights for policymakers and conservationists.